Keseimbangan Karir dan Keluarga Bagi Wanita Pekerja pada Perspektif Manajemen Konflik - Theresia Berlian Afrida; Prihatin Lumbanraja; Yeni Absah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Working women have the potential to experience conflict in carrying out all of their roles. This conflict has the potential to cause organizational conflict so that it must be managed from both sides. This study aims to analyze conflict and conflict management from 2 perspectives, working women and organization. Qualitative research with a descriptive approach was conducted with in-depth interviews and documentation of key informants of working women, direct supervisors, and supporting informants, which were analyzed using interactive model data analysis techniques. In carrying out their roles, working women have made efforts to balance, but it’s difficult to do. Supporting factors are social support from family, spouses, and coworkers. Differences in perceptions with spouses and coworkers are an inhibiting factor. Organizations perceive role conflict in 2 perceptions, direct supervisors and field employees. In the perception of direct supervisors, role conflict in women doesn’t affect the performance of the field and the organization as a whole. In the perception of field employees, role conflict causes jealousy, reluctance, delegation of tasks, and difficulty carrying out assignments due to changing team arrangements. Supporting factors for the organization are the existence of a communication system in the organization regardless of hierarchy and the sharing of knowledge between leaders regarding employee characteristics and conflict management. Differences regarding the conditions and problems of employees become an obstacle for organization to determine treatment standards. Organizational conflict handling strategies carried out are using persuasive and collaborative leadership styles, open communication with employees, collaboration and compromise conflict management styles.